Laminated self-supporting electrode material, preparation method thereof and application of laminated self-supporting electrode material in seawater electrolysis and oxygen evolution

By using stacked self-supporting electrode materials in electrolytic seawater, the anode corrosion problem is solved, the stability and efficiency of the oxygen production process of electrolytic seawater are achieved, and the development of the electrolytic seawater industry is promoted.

CN119913549APending Publication Date: 2025-05-02HUAZHONG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410974318.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has anode corrosion problems in electrolytic seawater, which leads to unstable oxygen production process of electrolytic seawater and limits the development of the electrolytic seawater industry.

Method used

A laminated self-supporting electrode material is designed to form a laminated nickel-iron sulfide laminated structure modified by cobalt hydroxide by growing nickel-iron sulfide on foamed nickel-iron sulfide laminated by electrodeposition.

Benefits of technology

The material exhibits excellent catalytic activity and stability in alkaline water and seawater, significantly reduces overpotentials, improves the oxidation performance of the electrode seawater, and maintains stable performance over long-term operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004954105670000081
    Figure BDA0004954105670000081
  • Figure HDA0004954105680000011
    Figure HDA0004954105680000011
  • Figure HDA0004954105680000012
    Figure HDA0004954105680000012
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts for oxygen production through seawater electrolysis, and particularly discloses a laminated self-supporting electrode material, a preparation method thereof and application of the laminated self-supporting electrode material to oxygen evolution through seawater electrolysis. The laminated self-supporting electrode material is a cobalt hydroxide modified nickel-iron sulfide, and a laminated composite structure is formed by the nickel-iron sulfide growing on a foamed nickel-iron substrate and a cobalt hydroxide nanosheet array. The preparation method comprises the following steps: S1, carrying out in-situ reaction on foamed ferronickel on a foamed ferronickel substrate in a sulfur source solution by adopting a hydrothermal method to generate ferronickel sulfide; and S2, modifying the cobalt hydroxide nanosheet array on the ferro-nickel sulfide by adopting an electro-deposition method. The invention relates to a cobalt hydroxide modified nickel-iron sulfide laminated self-supporting electrode material. As an alkaline water and seawater oxidation electrode, the composite material shows excellent catalytic activity and stability, and has potential application value in the aspect of developing a transition metal OER catalyst for electrolyzing seawater for oxygen evolution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts for electrolyzing seawater to produce oxygen, and specifically relates to a laminated self-supporting electrode material, a preparation method thereof, and an application of electrolyzing seawater to produce oxygen. Background Art

[0002] Among the many renewable energy sources, hydrogen (H2) is considered to be an ideal energy source with great application prospects due to its high energy density, simple chemical composition and environmental friendliness. However, the production of hydrogen is an important factor restricting its development. At present, hydrogen production technologies include fossil fuels, biomass and water electrolysis. Among them, water electrolysis has attracted much attention due to its environmental friendliness, sustainable development and easy industrialization. However, fresh water resources only account for 4% of the world's water resources. If fresh water is electrolyzed on a large scale, it will inevitably aggravate the problem of global fresh water shortage. Considering that the seawater resources on the earth are extremely abundant, the electrolysis of seawater to produce hydrogen is one of the important directions for the future development of hydrogen energy. However, there are a large number of chloride ions (Cl - ), these chloride ions will produce highly oxidizing hypochlorites during the seawater oxidation process, and will corrode the anode, which seriously hinders the long-term stable electrolysis of seawater. Studies have shown that alkaline seawater can make the thermodynamic potential of the oxygen evolution reaction (OER) 490mV lower than the thermodynamic potential of the chlorine evolution reaction (CER). In other words, an anode catalyst with sufficiently high OER activity can limit the occurrence of CER, effectively alleviate the corrosion of the anode, and is conducive to the long-term stable electrolysis of seawater. Therefore, it is necessary to design a highly active, highly selective and Cl-resistant anode catalyst. - The anode catalyst for seawater electrolysis is crucial to promoting the development of the seawater electrolysis industry.

[0003] As we all know, precious metal-based catalysts (such as IrO2 and RuO2) with excellent electrocatalytic performance are limited in large-scale application due to their high price, limited reserves and insufficient stability. Currently, nickel-iron-based electrocatalysts are regarded as a type of transition metal-based electrocatalyst with broad application prospects due to their low price, abundant reserves and outstanding performance in OER. However, they have insufficient performance and poor stability in the electrolysis of alkaline seawater. Summary of the invention

[0004] The purpose of the present invention is to provide a laminated self-supporting electrode material and its preparation method and application in electrolyzing seawater for oxygen evolution in view of the problems existing in the prior art. As an alkaline water and seawater oxidation electrode, it has excellent catalytic activity and stability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A laminated self-supporting electrode material is a cobalt hydroxide modified nickel iron sulfide, which is composed of nickel iron sulfide grown on a nickel iron foam substrate and a cobalt hydroxide nanosheet array to form a laminated composite structure.

[0007] According to the above scheme, the nickel atom content in the nickel-iron sulfide is 31.41 at% to 49.84 at%, the iron atom content is 8.12 at% to 18.47 at%, and the sulfur atom content is 32.37 at% to 54.23 at%.

[0008] According to the above scheme, the nickel iron sulfide in the laminated self-supporting electrode material contains Ni3S2 and (Fe, Ni)3S4; and the cobalt hydroxide is amorphous.

[0009] According to the above scheme, in the laminated self-supporting electrode material, nickel iron sulfide nanoblocks are in the form of mountain-shaped protrusions, forming a laminated composite structure with cobalt hydroxide nanosheet arrays. The size of the nickel iron sulfide nanoblocks is 700-900nm, and the thickness of the cobalt hydroxide nanosheets is 10-20nm.

[0010] According to the above scheme, the thickness of the nickel iron sulfide layer is 3 to 5 μm, and the thickness of the cobalt hydroxide layer is 3 to 4 μm.

[0011] The second aspect of the present invention provides a method for preparing a laminated self-supporting electrode material, comprising the following steps: Step S1: using a hydrothermal method to in-situ generate nickel-iron sulfide on a nickel-iron foam substrate in a sulfur source solution; Step S2: using an electrodeposition method to modify a cobalt hydroxide nanosheet array onto the nickel-iron sulfide.

[0012] In an optional scheme: the specific steps of step S1 are: placing the cleaned nickel-iron foam in a clarified solution containing a sulfur source, and using a hydrothermal method to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0013] In an optional scheme: the sulfur source solution is provided by thiourea, thioacetamide or sodium sulfide with a concentration of 0.05-0.25 mol / L.

[0014] In an optional scheme: the hydrothermal conditions in the hydrothermal method are 120-220° C. and the hydrothermal time is 4-24 hours.

[0015] In an optional scheme: the specific steps of step S2 are: placing nickel iron sulfide in a 2+ The solution is used as the working electrode and electrodeposition is carried out at a constant current density. After the reaction is completed, it is rinsed clean and dried in an oven to obtain a cobalt hydroxide-modified nickel-iron sulfide laminated self-supporting electrode material.

[0016] In an alternative embodiment: the Co 2+The solution is selected from Co(NO3)2, CoCl2, CoSO4, CoCO3 or Co3(PO4)2; the Co 2+ The concentration of the solution is 0.05~0.25mol / L.

[0017] In an optional embodiment: the electrodeposition condition in the electrodeposition method is 5 to 25 mA / cm 2 , electrodeposition time is 300 to 1000 s.

[0018] The third aspect of the present invention provides the use of the above-mentioned laminated self-supporting electrode material in electrolysis of alkaline water or seawater for oxygen evolution.

[0019] The present invention provides a laminated self-supporting electrode material, which is a nickel iron sulfide modified by cobalt hydroxide. The nickel iron sulfide grown on a nickel iron foam substrate and a cobalt hydroxide nanosheet array form a laminated composite structure, which can fully expose active sites. Specifically, the nickel iron sulfide surface can be modified by electrodeposition to form a cobalt hydroxide modified nickel iron sulfide (NiFeS x @Co(OH)2) stacked structure; nickel iron sulfide ensures the stability and conductivity of the catalyst, and also has good corrosion resistance, which can maintain the long-term structural stability of the catalyst during the electrolysis of seawater; through the modification of cobalt hydroxide, cobalt hydroxide itself has excellent water oxidation ability, and NiFeS x The electronic interaction between Co(OH)2 and Co(OH)2 leads to charge redistribution at their coupling interface. 3+ The increase is beneficial to the adsorption of hydroxide ions, greatly promoting the reaction kinetics and selectivity of the oxygen evolution reaction in seawater electrolysis, improving the OER activity and selectivity of the catalyst, and ultimately significantly improving the seawater oxidation performance of the electrode.

[0020] Beneficial effects of the present invention:

[0021] 1. The cobalt hydroxide modified nickel iron sulfide laminated self-supporting electrode material provided by the present invention, as an alkaline water and seawater oxidation electrode, exhibits excellent catalytic activity and stability, and has potential application value in the development of transition metal OER catalysts for electrolysis of seawater oxygen evolution. 2 At a current density of 500 mA / cm2, the overpotential required in alkaline aqueous solution is as low as 174, 223 and 264 mV, and the overpotential required in alkaline seawater is 208, 244 and 308 mV, which is much lower than that of the nickel iron sulfide sample without cobalt hydroxide modification. 2 After running for 300 hours at a constant current density, its seawater oxidation performance did not show obvious attenuation, and its performance was excellent.

[0022] 2. The present invention innovatively develops a unique two-step hydrothermal plus electrodeposition method, in which dense nickel-iron sulfide is in situ grown on nickel-iron foam as a self-supporting template by a hydrothermal method, and then cobalt hydroxide is deposited on the nickel-iron sulfide by an electrodeposition method to form a cobalt hydroxide-modified nickel-iron sulfide stacked structure. The preparation method is simple and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The nickel-iron sulfide (denoted as NiFeS) grown on the nickel-iron foam substrate after hydrothermal reaction x ) Scanning electron microscope (SEM) images at different magnifications.

[0024] Figure 2 SEM images of nickel-iron sulfide modified with cobalt hydroxide after electrodeposition at different magnifications.

[0025] Figure 3 (a) is NiFeS x Distribution diagram of Fe, Ni and S elements; (b) NiFeS x Distribution diagram of Fe, Ni and S elements in the cross section.

[0026] Figure 4 (a) is NiFeS x @Co(OH)2 distribution of Fe, Co, Ni, S and O elements; (b) NiFeS x @Distribution diagram of Fe, Co, Ni and S elements in the Co(OH)2 cross section.

[0027] Figure 5 (a) is NiFeS x X-ray diffraction pattern (XRD); (b) NiFeS x @Co(OH)2 XRD pattern; (c) NiFeS x @Co(OH)2 and NiFeS x Raman spectra comparison of NiFeS x @Co 2p energy level diagram of Co(OH)2 and Co(OH)2 by X-ray photoelectron spectroscopy (XPS);

[0028] Figure 6 NiFeS x Comparison of OER performance of @Co(OH)2 in alkaline aqueous electrolyte (1 mol / L potassium hydroxide) with other samples; (a) linear sweep voltammetry (LSV) curve; (b) comparison of overpotentials at different current densities; (c) Tafel slope; (d) electrochemical impedance spectroscopy (EIS);

[0029] Figure 7Comparison of the OER performance of NiFeSx@Co(OH)2 in alkaline seawater electrolyte (1 mol / L potassium hydroxide + seawater) and other samples; (a) linear sweep voltammetry (LSV) curve; (b) overpotential comparison at different current densities; (c) at 500 mA / cm 2 Performance curves for stable testing at current density.

[0030] Figure 8 NiFeS x @Co(OH)2 and NiFeS x Plot of the Faraday efficiency during the oxygen evolution reaction in alkaline seawater. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0032] Example 1

[0033] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0034] An embodiment of the present invention provides a laminated self-supporting electrode material, which is nickel iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel iron sulfide and cobalt hydroxide is grown on a nickel iron foam substrate by a two-step method of hydrothermal and electrodeposition.

[0035] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0036] (1) The cleaned nickel-iron foam was placed in 60 mL of a clear solution containing 0.2 mol / L thiourea and reacted at 200° C. for 12 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain nickel-iron sulfide (denoted as NiFeS) grown on the nickel-iron foam. x ).

[0037] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.15 mol / L Co(NO3)2·6H2O was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 15 mA / cm 2 The electrodeposition was carried out at a constant current density of 1.50 and a constant time of 800 s. After the reaction was completed, the nickel iron sulfide modified with cobalt hydroxide (denoted as NiFeS x @Co(OH)2).

[0038] (3) The prepared NiFeS x A three-electrode system consisting of @Co(OH)2 as the working electrode, mercury oxide electrode as the reference electrode and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0039] Figure 1 NiFeS x SEM images at different magnifications show that a uniform layer of nickel-iron sulfide mountain-shaped protrusion nanoblock arrays with a size of 700 to 900 nm is evenly grown on the nickel-iron foam substrate.

[0040] Figure 2 NiFeS x @Co(OH)2 SEM images at different magnifications show that a dense array of cobalt hydroxide nanosheets is deposited on the surface of nickel-iron sulfide, and the thickness of the nanosheets is extremely thin, only 10 to 20 nm.

[0041] Figure 3 (a) NiFeS x According to the EDS test results, Fe, Ni and S elements are evenly distributed, with the nickel atomic content being 35.82at%, the iron atomic content being 14.25at%, and the sulfur atomic content being 49.07at%. Figure 3 (b) NiFeS x The EDS test results of the cross section showed that the thickness of the nickel-iron sulfide layer was 3 to 5 μm.

[0042] Figure 4 (a) NiFeS x @The EDS test results of Co(OH)2 show that Fe, Co, Ni, O and S elements are evenly distributed on the composite structure, among which: the nickel atom content is 24.82at%, the iron atom content is 9.32at%, the cobalt atom content is 10.31at%, and the sulfur atom content is 32.15at%. Figure 4 (b) NiFeS x @Co(OH)2 cross-section EDS test results further revealed that the thickness of the nickel-iron sulfide layer was 3-5 μm, and the thickness of the cobalt hydroxide layer was 3-4 μm. The thickness of the nickel-iron sulfide layer remained almost unchanged before and after the electrodeposition of cobalt hydroxide, indicating that the electrodeposition of cobalt hydroxide did not affect the nickel-iron sulfide layer.

[0043] Figure 5 (a) XRD pattern of NiFeS x The characteristic peaks match those of (Ni,Fe)(PDF#12-0736), Ni3S2(PDF#02-0722) and (Fe,Ni)3S4 JCPDS#11-095, indicating the successful synthesis of nickel-iron sulfide. Figure 5 (b) It can be seen that NiFeS x @Co(OH)2XRD diffraction peaks did not show significant changes before and after electrodeposition. NiFeS x @Co(OH)2 did not show obvious diffraction peak signal of Co(OH)2(PDF#02-0925), which on the one hand indicates that electrodeposition did not affect the lattice structure of nickel-iron sulfide, and on the other hand indicates that the electrodeposited cobalt hydroxide nanosheets are amorphous, so no diffraction peak signal of Co(OH)2(PDF#02-0925) appeared. Figure 5 (c) Display of NiFeS x and NiFeS x @Co(OH)2 Raman spectrum comparison shows that NiFeS x The Raman spectrum shows obvious metal-sulfur characteristic signals, and NiFeS is formed by electrodeposition. x @After the Co(OH)2 composite structure, the Raman spectrum retains the original metal-sulfur characteristic signals, and also shows two Raman characteristic signals, O-Co-O and Co-O, belonging to Co(OH)2. Figure 5 (d) shows the two samples (Co(OH)2 / NFF obtained by direct electrodeposition of Co(OH)2 on nickel iron foam, and NiFeS x @Co(OH)2)XPS spectra of Co 2p energy level, Co(OH)2 / NFF catalyst 3+ With Co 2+ The peak area is 0.62:1, and the electrodeposition of Co(OH)2 onto NiFeS x The NiFeS x @Co(OH)2 3+ With Co 2+ The peak area increased to 0.976:1, which is due to NiFeS x The electronic interaction between Co(OH)2 and Co(OH)2 leads to charge redistribution at their coupling interface. 3+ The high-valent Co is often the active site in the OER reaction and is conducive to the adsorption of hydroxide ions, thereby improving the OER activity and selectivity of the catalyst.

[0044] Figure 6 (a) and (b) show NiFeS x 、NiFeS x Linear sweep voltammetry (LSV) curves of @Co(OH)2 and commercial IrO2 samples in 1 mol / L potassium hydroxide solution and detailed OER overpotential comparison diagram. It can be found that the introduction of Co(OH)2 significantly improves the NiFeSx The OER performance is 10, 100 and 500 mA / cm 2 At a current density of 1.34, the overpotential required in alkaline aqueous solution is as low as 174, 223 and 264 mV, which is much better than the commercial IrO2 samples. The Tafel slopes of these samples are further calculated as Figure 6 (c) shows NiFeS x The @Co(OH)2 sample has a low Tafel slope of 36.41 mV / dec, indicating that Co(OH)2 modification is beneficial to promote faster OER reaction kinetics. Figure 6 (d) Electrochemical impedance spectroscopy of NiFeS x @Co(OH)2's smaller charge transfer resistance reflects that the deposition of Co(OH)2 is also beneficial to improve the NiFeS x conductivity, thus promoting rapid electron transfer on the catalyst.

[0045] Figure 7 The electrochemical performance test results of the samples in alkaline seawater electrolyte (1 mol / L potassium hydroxide + seawater) are shown. Figure 7 (a) and (b) show NiFeS x and NiFeS x LSV curve of @Co(OH)2 sample in alkaline seawater electrolyte and comparison of overpotential at different current densities. x , NiFeS x The @Co(OH)2 samples have excellent OER performance in alkaline seawater at 10, 100 and 500 mA / cm 2 At current densities of , the required OER overpotentials are only as low as 209, 244, and 307 mV, as shown in Table 1. Figure 7 (c) shows the stability test results. The NiFeSx without electrodeposition is 500mA / cm 2 The current density of NiFeS can only run for about 15 hours, while x @Co(OH)2 sample at 500mA / cm 2 It can run stably for 300 hours at a constant current density without obvious performance degradation.

[0046] Figure 8 The Faradaic efficiency of the samples and the control samples in the electrolysis of seawater for oxygen evolution is shown. x @Co(OH)2 exhibited a Faradaic efficiency of 98.93%, while the control sample NiFeS had a Faradaic efficiency of only 92.83%, showing that NiFeS x @Co(OH)2 has extremely high OER selectivity.

[0047] Example 2

[0048] An embodiment of the present invention provides a laminated self-supporting electrode material, which is a nickel-iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel-iron sulfide and cobalt hydroxide is grown on a nickel-iron foam substrate by a two-step method of hydrothermal and electrodeposition. The nickel-iron sulfide has a nickel atom content of 49.84 at%, an iron atom content of 18.47 at%, and a sulfur atom content of 32.37 at%. In the nickel-iron sulfide modified with cobalt hydroxide, the nickel atom content is 29.57 at%, the iron atom content is 10.24 at%, the cobalt atom content is 16.14 at%, and the sulfur atom content is 19.78 at%.

[0049] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0050] (1) The cleaned nickel-iron foam is placed in 60 mL of a clear solution containing 0.15 mol / L thioacetamide, and reacted at 120° C. for 18 h using a hydrothermal method. After the reaction is completed and cooled to room temperature, the foam is rinsed and dried in an oven to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0051] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.05 mol / L CoCl2·6H2O was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 25 mA / cm 2 The electrodeposition preparation is carried out at a constant current density of 500 s and a constant time of 500 s. After the reaction is completed, the mixture is rinsed and dried in an oven to obtain nickel iron sulfide modified with cobalt hydroxide.

[0052] (3) The prepared NiFeS x The three-electrode system consisting of @Co(OH)2 as the working electrode, mercuric oxide electrode as the reference electrode, and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance. The sample was tested at 10, 100, and 500 mA / cm 2 The overpotential of seawater oxidation at current density is shown in Table 1.

[0053] Example 3

[0054] An embodiment of the present invention provides a laminated self-supporting electrode material, which is a nickel-iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel-iron sulfide and cobalt hydroxide is grown on a nickel-iron foam substrate by a two-step method of hydrothermal and electrodeposition. The nickel-iron sulfide has a nickel atom content of 33.23 at%, an iron atom content of 12.54 at%, and a sulfur atom content of 54.23 at%. In the nickel-iron sulfide modified with cobalt hydroxide, the nickel atom content is 21.37 at%, the iron atom content is 10.24 at%, the cobalt atom content is 15.31 at%, and the sulfur atom content is 19.14 at%.

[0055] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0056] (1) The cleaned nickel-iron foam is placed in 60 mL of a clear solution containing 0.25 mol / L sodium sulfide, and reacted at 220° C. for 24 h using a hydrothermal method. After the reaction is completed and cooled to room temperature, the foam is rinsed and dried in an oven to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0057] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.10 mol / L CoSO4·7H2O was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 5 mA / cm 2 The electrodeposition preparation was carried out at a constant current density of 300 s and a constant time of 300 s. After the reaction was completed, the mixture was rinsed and dried in an oven to obtain nickel iron sulfide modified with cobalt hydroxide.

[0058] (3) The prepared NiFeS x The three-electrode system consisting of @Co(OH)2 as the working electrode, mercuric oxide electrode as the reference electrode, and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance. The sample was tested at 10, 100, and 500 mA / cm 2 The overpotential of seawater oxidation at current density is shown in Table 1.

[0059] Example 4

[0060] An embodiment of the present invention provides a laminated self-supporting electrode material, which is a nickel-iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel-iron sulfide and cobalt hydroxide is grown on a nickel-iron foam substrate by a two-step method of hydrothermal and electrodeposition. The nickel-iron sulfide has a nickel atom content of 43.71 at%, an iron atom content of 8.12 at%, and a sulfur atom content of 48.17 at%. In the nickel-iron sulfide modified with cobalt hydroxide, the nickel atom content is 32.57 at%, the iron atom content is 5.14 at%, the cobalt atom content is 8.12 at%, and the sulfur atom content is 15.22 at%.

[0061] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0062] (1) The cleaned nickel-iron foam is placed in 60 mL of a clear solution containing 0.05 mol / L thiourea, and reacted at 180° C. for 6 h using a hydrothermal method. After the reaction is completed and cooled to room temperature, the foam is rinsed and dried in an oven to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0063] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.25 mol / L CoCO3 was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 20 mA / cm 2 The electrodeposition preparation is carried out at a constant current density of 1000 s and a constant time of 1000 s. After the reaction is completed, the mixture is rinsed and dried in an oven to obtain nickel iron sulfide modified with cobalt hydroxide.

[0064] (4) The prepared NiFeS x The three-electrode system consisting of @Co(OH)2 as the working electrode, mercuric oxide electrode as the reference electrode, and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance. The sample was tested at 10, 100, and 500 mA / cm 2 The overpotential of seawater oxidation at current density is shown in Table 1.

[0065] Example 5

[0066] An embodiment of the present invention provides a laminated self-supporting electrode material, which is a nickel-iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel-iron sulfide and cobalt hydroxide is grown on a nickel-iron foam substrate by a two-step method of hydrothermal and electrodeposition. The nickel-iron sulfide has a nickel atom content of 31.41 at%, an iron atom content of 17.76 at%, and a sulfur atom content of 50.83 at%. In the nickel-iron sulfide modified with cobalt hydroxide, the nickel atom content is 18.94 at%, the iron atom content is 11.32 at%, the cobalt atom content is 15.61 at%, and the sulfur atom content is 30.65 at%.

[0067] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0068] (1) The cleaned nickel-iron foam is placed in 60 mL of a clear solution containing 0.10 mol / L thioacetamide, and reacted at 160° C. for 4 h using a hydrothermal method. After the reaction is completed and cooled to room temperature, the foam is rinsed and dried in an oven to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0069] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.20 mol / L Co3(PO4)2·8H2O was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 10 mA / cm 2 The electrodeposition preparation was carried out at a constant current density of 1.5 and a constant time of 400 s. After the reaction was completed, the mixture was rinsed and dried in an oven to obtain nickel iron sulfide modified with cobalt hydroxide.

[0070] (3) The prepared NiFeS x The three-electrode system consisting of @Co(OH)2 as the working electrode, mercuric oxide electrode as the reference electrode, and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance. The sample was tested at 10, 100, and 500 mA / cm 2 The overpotential of seawater oxidation at current density is shown in Table 1.

[0071] Example 6

[0072] An embodiment of the present invention provides a laminated self-supporting electrode material, which is a nickel-iron sulfide modified with cobalt hydroxide. A laminated composite structure of nickel-iron sulfide and cobalt hydroxide is grown on a nickel-iron foam substrate by a two-step method of hydrothermal and electrodeposition. The nickel-iron sulfide has a nickel atom content of 47.09 at%, an iron atom content of 12.72 at%, and a sulfur atom content of 40.19 at%. In the nickel-iron sulfide modified with cobalt hydroxide, the nickel atom content is 26.98 at%, the iron atom content is 7.36 at%, the cobalt atom content is 14.13 at%, and the sulfur atom content is 23.08 at%.

[0073] The present invention also discloses a method for preparing the laminated self-supporting electrode material, the steps of which are as follows:

[0074] (1) The cleaned nickel-iron foam is placed in 60 mL of a clear solution containing 0.25 mol / L sodium sulfide, and reacted at 100° C. for 14 h using a hydrothermal method. After the reaction is completed and cooled to room temperature, the nickel-iron foam is rinsed and dried in an oven to obtain nickel-iron sulfide grown on the nickel-iron foam.

[0075] (2) Cobalt hydroxide nanosheets were deposited on nickel iron sulfide by electrodeposition: 0.15 mol / L Co(NO3)2·6H2O was dissolved in 60 mL of deionized water and stirred to obtain a clear solution. Nickel iron sulfide was placed in the clear solution and charged at 10 mA / cm 2 The electrodeposition preparation was carried out at a constant current density of and a constant time of 600 s. After the reaction was completed, the mixture was rinsed and dried in an oven to obtain nickel iron sulfide modified with cobalt hydroxide.

[0076] (3) The prepared NiFeS x The three-electrode system consisting of @Co(OH)2 as the working electrode, mercuric oxide electrode as the reference electrode, and graphite rod electrode as the counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance. The sample was tested at 10, 100, and 500 mA / cm 2 The overpotential of seawater oxidation at current density is shown in Table 1.

[0077] Table 1 NiFeS prepared in different embodiments x @Summary of the alkaline seawater oxidation performance of Co(OH)2 samples

[0078]

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A laminated self-supporting electrode material, characterized in that: The material is a cobalt hydroxide-modified nickel iron sulfide, which forms a laminated composite structure consisting of nickel iron sulfide grown on a nickel iron foam substrate and a cobalt hydroxide nanosheet array.

2. The laminated self-supporting electrode material according to claim 1, characterized in that: The nickel-iron sulfide has a nickel atom content of 31.41 at% to 49.84 at%, an iron atom content of 8.12 at% to 18.47 at%, and a sulfur atom content of 32.37 at% to 54.23 at%.

3. The laminated self-supporting electrode material according to claim 1, characterized in that: The nickel iron sulfide in the laminated self-supporting electrode material contains Ni3S2 and (Fe, Ni)3S4; the cobalt hydroxide is amorphous.

4. The laminated self-supporting electrode material according to claim 1, characterized in that: Nickel-iron sulfide nanoblocks are in the form of mountain-shaped protrusions, which grow in situ on nickel-iron foam, forming a laminated composite structure with the cobalt hydroxide nanosheet array on the nickel-iron sulfide layer. The size of the nickel-iron sulfide nanoblocks is 700-900nm, and the thickness of the cobalt hydroxide nanosheets is 10-20nm.

5. The laminated self-supporting electrode material according to claim 1, characterized in that: The thickness of the nickel-iron sulfide layer is 3 to 5 μm, and the thickness of the cobalt hydroxide layer is 3 to 4 μm.

6. The method for preparing the laminated self-supporting electrode material according to claim 1, characterized in that: Includes the following Steps: Step S1: In situ generate nickel-iron sulfide on a nickel-iron foam substrate in a sulfur source solution by a hydrothermal method; Step S2: Modify the cobalt hydroxide nanosheet array onto the nickel-iron sulfide by an electrodeposition method.

7. The preparation method according to claim 6, characterized in that: The specific steps of step S1 are: placing the cleaned nickel-iron foam in a clarified solution containing a sulfur source, and obtaining nickel-iron sulfide grown on the nickel-iron foam by a hydrothermal method; The specific steps of step S2 are: placing nickel iron sulfide in a solution containing Co 2+ The solution is used as the working electrode and electrodeposition is carried out at a constant current density. After the reaction is completed, it is rinsed clean and dried in an oven to obtain a cobalt hydroxide-modified nickel-iron sulfide laminated self-supporting electrode material.

8. The preparation method according to claim 6, characterized in that: The electrodeposition conditions in the electrodeposition method are 5 to 25 mA / cm 2 , electrodeposition time is 300 to 1000 s.

9. The preparation method according to claim 6, characterized in that: The sulfur source solution is provided by thiourea, thioacetamide or sodium sulfide with a concentration of 0.05-0.25 mol / L; the hydrothermal conditions in the hydrothermal method are 120-220° C. and the hydrothermal time is 4-24 hours; The Co 2+ The solution is selected from Co(NO3)2, CoCl2, CoSO4, CoCO3 or Co3(PO4)2; the Co 2+ The concentration of the solution is 0.05~0.25mol / L.

10. Use of the laminated self-supporting electrode material according to claim 1 in electrolysis of alkaline water or seawater for oxygen evolution.